Integrated RNAi screening identifies the NEDDylation pathway as a synergistic partner of azacytidine in acute myeloid leukemia - Klosner, Justine; Agelopoulos, Konstantin; Rohde, Christian; Göllner, Stefanie; Schliemann, Christoph; Berdel, Wolfgang E.; Müller-Tidow, Carsten (Scientific reports, 2021)
Treatment of acute myeloid leukemia (AML) remains challenging and novel targets and synergistic therapies still need to be discovered. We performed a high-throughput RNAi screen in three different AML cell lines and primary human leukemic blasts to identify genes that synergize with common antileukemic therapies. We used a pooled shRNA library that covered 5043 different genes and combined transfection with exposure to either azacytidine or cytarabine analog to the concept of synthetic lethality. Suppression of the chemokine CXCL12 ranked highly among the candidates of the cytarabine group. Azacytidine in combination with suppression of genes within the neddylation pathway led to synergistic results. NEDD8 and RBX1 inhibition by the small molecule inhibitor pevonedistat inhibited leukemia cell growth. These findings establish an in vitro synergism between NEDD8 inhibition and azacytidine in AML. Taken together, neddylation constitutes a suitable target pathway for azacytidine combination strategies.